Adverse childhood experiences and potential pathways to filicide perpetration: A systematic search and review. (8th February 2022) - Frederick, John; Devaney, John; Alisic, Eva
Abstract: Filicides, where children are killed by their parents or stepparents, are uncommon occurrences, which are committed by both paternal and maternal perpetrators. The aim of this paper is to explore to what extent the antecedents of filicides can be traced back to one of the factors identified within the literature – the adverse childhood experiences of the perpetrators – and what this might mean for the way that services seek to intervene to safeguard and support children in precarious situations. Systematic searches were used to retrieve relevant articles in six electronic databases: AMED, CINAHL, Criminal Justice Abstracts, Medline (PubMed), PsycINFO and SCOPUS. Key findings were that numerous studies reported significant levels of complex, multiple and sustained experiences of childhood adversity for many perpetrators, and that various potential pathways to filicide perpetration may emanate from such experiences. This review suggests that evidence‐based interventions should be made readily available early in life to persons experiencing adverse childhood experiences, together with supportive services to those who become parents and carers. Such support may help prevent the compounding of adversity over time, thereby reducing the potential for risk of harm and possible tragic outcomes for their dependent children. Key Practitioner Messages: Evidence‐based interventions should be made readily available early in life to persons experiencing adverse childhood experiences, together with supportive services to those who become parents and carers. Interventions need to provide early help to children whilst also incorporating a long‐term view of support. Attention to planning and co‐ordination issues between varied services and practitioners can help overcome fragmentation, duplication and gaps in services.